PENGARUH TEKNIK SELF MANAGEMENT UNTUK MENGURANGI PERILAKU KECANDUAN GADGET SISWA SMK NEGERI 1 PEKANBARU - Astiti, Windi; Yakub, Elni; Umari, Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to examine the effect of self management techniques on gadget addiction behavior of students of SMK Negeri 1 Pekanbaru. This type of research is a quantitative study with an experimental method using the research design One-Group Pretest-Posttest Design. The measuring instrument used in this study is the scale of measurement of gadget addiction behavior which consists of 50 items before the validity, and after divalidity there are 41 valid items obtained with validity of 0.560 and reliability of 0.934. The subjects of this study were 7 students of SMK Negeri 1 Pekanbaru who were identified as having high levels of addictive gadget behavior. The data analysis technique used is non-parametric statistical techniques using the Wilcoxon test. The results of the study proved that the research hypothesis was accepted. For this reason, it can be concluded that there are differences in gadget addiction behavior scores before and after being given treatment in the form of self management techniques. From the results of Rank Spearman test obtained r = 0.821 while the correlation coefficient r2 = 0.67. Thus there is the effect of self management techniques on student gadget addiction behavior by 67% at SMK Negeri 1 Pekanbaru.Key Words: Self management, gadget addiction behavior of students SMK